Emerging Adjuvants for Cancer Immunotherapy - Hu, Hong-Guo; Li, Yan-Mei (Frontiers in Chemistry, 2020)
Cancer is a deadly disease threating the life of human beings, and the immunotherapy showed a potent efficiency for cancer treatment. Adjuvants play crucial roles in the activation of immune system which is necessary for cancer immunotherapy, whether used alone or in combination with other agents, especially in the construction of therapeutic cancer vaccines. Adjuvants are supposed to activate antigen presenting cells (APCs) and promote the presentation of antigen epitopes on major histocompatibility complex (MHC), and further enhance adaptive immune response like cytotoxic T lymphocyte (CTL) for cancer cells killing. However, the activity and security impeded the application of adjuvants. In the last few years, researchers have been trying to develop safe and efficient adjuvants for cancer immunotherapy, and many compounds (including inorganic compound, organic molecule, polymer and colloid) have been identified and optimized as agonists of many pathways. In this minireview, we focused on the discovery or structure design of emerging adjuvants and discuss how these findings benefit of health care.